2009
DOI: 10.1080/09540120902889926
|View full text |Cite
|
Sign up to set email alerts
|

Economic and quality of life outcomes of antiretroviral therapy for HIV/AIDS in developing countries: a systematic literature review

Abstract: The impacts of antiretroviral therapy (ART) on quality of life, mental health, labor productivity, and economic wellbeing for people living with HIV/AIDS in developing countries are only beginning to be measured. We conducted a systematic literature review to analyze the effect of ART on these economic and quality of life indicators in developing countries and assess the state of research on these topics. We searched Ovid/Medline, PubMed, Psych Info, Web of Science, Google Scholar, and the abstract database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 25 publications
6
85
3
2
Order By: Relevance
“…As with some other researchers, I found that HIV symptoms (Préau et al, 2004), depression scores on a rating scale (Beard et al, 2009;Jelsma et al, 2005;Judd et al, 2000;Stangl et al, 2007), and internalized stigma reduced over time, whereas CD4 cell counts (Bhargava & Booysen, 2010;Langius-Eklöf et al, 2009), adherence to ART (Maqutu, Zewotir, North, Naidoo, & Grobler, 2010), and social support increased over 20 months (Burgoyne & Renwick, 2004). Social support has been shown to positively influence quality of life outcomes by mediating depression (Jia et al, 2005;Stangl et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…As with some other researchers, I found that HIV symptoms (Préau et al, 2004), depression scores on a rating scale (Beard et al, 2009;Jelsma et al, 2005;Judd et al, 2000;Stangl et al, 2007), and internalized stigma reduced over time, whereas CD4 cell counts (Bhargava & Booysen, 2010;Langius-Eklöf et al, 2009), adherence to ART (Maqutu, Zewotir, North, Naidoo, & Grobler, 2010), and social support increased over 20 months (Burgoyne & Renwick, 2004). Social support has been shown to positively influence quality of life outcomes by mediating depression (Jia et al, 2005;Stangl et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…These findings were supported in more recent studies conducted in South Africa (Bhargava & Booysen, 2010) and in other Southern African countries (Greeff et al, 2010). Beard et al (2009) further observed that most researchers in developing countries have not yet assessed economic and quality-of-life outcomes of therapy beyond the first year; therefore, longitudinal outcomes are still unknown. In studies with longitudinal outcomes conducted in high-income countries over a period of 2 years or more it has been found that there was significant clinical improvement and that HRQoL was either reduced, sustained, or improved (Burgoyne, Rourke, Behrens, & Salit, 2004;Eriksson et al, 2005;Judd et al, 2000;Langius-Eklöf, Lidman, & Wredling, 2009;Préau et al, 2004).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…A systematic review of economic and quality-of-life outcomes of ARV therapy for HIV/AIDS in developing countries [25] did not include any modeling studies. However, a recent trend in health economics literature towards use of short-term treatment comparisons using a cost-effectiveness frontier (CEF) [26][27][28] is reflected in Economic modeling of HIV treatments Simpson 243 several ARV studies.…”
Section: Recent Findings: Current Economic Models In Hiv/aidsmentioning
confidence: 99%
“…The introduction of combination antiretroviral therapy (cART) around 1996 had a huge impact on the management of acquired immunodeficiency syndrome (AIDS), and resulted in increased quality of life and lifespan of seropositive individuals. 2,3 However, several limitations of currently available drugs, namely their toxicity and poor pharmacokinetics, the need to be used for prolonged periods of time (if not chronically), and the emergence of viral resistance, still jeopardize the optimal efficacy of cART. 4 Of particular importance is the poor bioavailability of several anti-HIV drugs at viral reservoir sites, such as the central nervous system (CNS), in special brain macrophages and microglia cells, when using available dosage forms.…”
Section: Introductionmentioning
confidence: 99%